2013
DOI: 10.1098/rspb.2012.2371
|View full text |Cite
|
Sign up to set email alerts
|

Females roam while males patrol: divergence in breeding season movements of pack-ice polar bears ( Ursus maritimus )

Abstract: Intraspecific differences in movement behaviour reflect different tactics used by individuals or sexes to favour strategies that maximize fitness. We report movement data collected from n ¼ 23 adult male polar bears with novel ear-attached transmitters in two separate pack ice subpopulations over five breeding seasons. We compared movements with n ¼ 26 concurrently tagged adult females, and analysed velocities, movement tortuosity, range sizes and habitat selection with respect to sex, reproductive status and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 45 publications
10
60
0
Order By: Relevance
“…Our analyses, which also included harvest recoveries of both sexes, did not indicate vastly different movement between males and females. Previous studies in BB also indicated that both sexes utilize the same habitats in spring (Laidre et al., 2013). We therefore suggest our satellite telemetry data are a representative index of broad population movement patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses, which also included harvest recoveries of both sexes, did not indicate vastly different movement between males and females. Previous studies in BB also indicated that both sexes utilize the same habitats in spring (Laidre et al., 2013). We therefore suggest our satellite telemetry data are a representative index of broad population movement patterns.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated that females traveled 51.6 AE 47.0 (SD) km over a 7 day period (n = 13,241 movement measurements). Collar-based movement data were not available for males in this region, but Laidre et al (2012) found no difference in movement rates of males and females in the spring.…”
Section: Objective 1: Spatial and Temporal Variation In Fasting Behmentioning
confidence: 99%
“…Our approach assumes that our sample of adult female movements is also representative of male movements. While not specifically addressed for polar bears in our study region, Laidre et al (2013) found that males and females of two separate polar bear populations exhibited similar habitat selection patterns and 4- Fig. 3.…”
Section: Discussionmentioning
confidence: 98%